Analisis Maraknya Eksploitasi Buruh Anak pasca Liberalisasi Perdagangan di Tiongkok - Sukmatika, Anak Agung Yumas (HUMANIORUM, 2024)
This study employs Marxism theory to examine the factors contributing to the escalation of child labor in China. China has undergone substantial economic growth since the implementation of trade liberalization and economic reform in 1978. Presently, China holds the position of being the world's second-largest economy following the United States (US). Nevertheless, the prevalence of child labor has risen due to pronounced economic disparities between urban and rural areas coupled with a demand for low-cost labor in the industrial sector. This study employs a qualitative method with a literature review approach to analyze non-numeric and descriptive data from various literature sources, including books, journal articles, and research reports. This study demonstrates that trade liberalization has exacerbated labor exploitation in China. Local governments as well as businesses frequently disregard regulations that prohibit child labor in order to maximize their profits. Furthermore, there exists a pervasive perception that children are economic assets rather than individuals requiring care and education. Many Chinese families rely on their children as the primary means of economic sustenance for the family, neglecting their educational needs. The findings of this research indicate persistent and worsening exploitation of child labor contrary to expectations of improved well-being through economic advancement. Ultimately, the fundamental tenets of Marxism, such as historical materialism, economic determinism, and false consciousness, are crucial for comprehending the rise of child labor in China.